Evaluating the risk of listeriosis through genotypic profiling of potentially hazardous strains isolated from local food market - lamiaa Fahmy; Hebatallah Amin (Microbes and Infectious Diseases)
Background: Listeriosis is a serious food-borne disease caused by Listeria monocytogenes pathogen that causes fatal systemic infections in the elderly and immunocompromised people. L. monocytogenes can be transferred from contaminated ready-to-eat or frozen foods, frozen vegetables and fruits. This study aimed to investigate the most prevalent serotypes of L. monocytogenes isolates in frozen food products in Egypt, their phenotypic and genotypic antimicrobial resistance, biofilm formation, as well as virulence encoding genes. Methods: A total of 331 frozen food product samples were randomly chosen from various marketplaces and cultured for the presence of L. monocytogenes. The antibiogram of the isolated L. monocytogenes was assessed using the Kirby–Bauer disk diffusion method. Polymerase chain reaction (PCR) was performed to detect four antimicrobial resistance encoding genes and seven virulence genes. A multiplex PCR assay was preformed. Results: L. monocytogenes was found in 14.2% (47/331) of the examined samples, and the most predominant serotypes belonged to molecular sero-groups 1/2a-3a. L. monocytogenes bacteria showed high phenotypic resistance rates to ampicillin (91%), cefotaxime (87%) and clindamycin (66%). Strong and moderate biofilm producers accounted for 21.4% and 11.9% of isolates, respectively. The most commonly detected genetic markers of resistance were strB and tetA genes (70%). The virulence genes; plcB, prs-prfA, iap and hlyA genes, were detected in 90%,87%, 87% and 30% of the isolates, respectively, while plc A, prfA and flA genes were detected in 83%, 97% and 90% of the isolates, respectively. Conclusion: L. monocytogenes food pathogen exists with considerable rates in frozen products, which may seriously threaten public health.